STUDY OF THE EFFECT OF MODIFIERS WITH ULTRADISPERSED PARTICLES IN THE COATING OF THE ELECTRODE FOR MANUAL ARC WELDING ON THE TECHNOLOGICAL PARAMETERS IN MANUFACTURE OF THE ELECTRODE - N. I. Urbanovich; V. V. Melnichenko; K. E. Baranovsky; E. V. Rozenberg; A. A. Radchenko; Z. V. Ignatovich (Литьë и металлургия)
It is established that inclusion of the modifier into the electrode coating allowed to change the grains of the weld metal from 20–60 to 10–30 mm, to change its morphology and to improve the welding-technological properties of the coated electrode. It is shown that the modifying additive introduced into the coating of a welding electrode containing ultrafine particles in an amount of 1% of the weight of the dry charge had not deteriorated the technological parameters during manufacture, and the integral index of the different thickness (Desp) of electrodes with standard and experimental coatings did not add to the accepted value of 0.05. This indicates that the quality of the lubricating mass, its properties, the stability of the mass flow from the spinneret are satisfactory for both batches.